The Aurora B Kinase in Chromosome Bi-Orientation and Spindle Checkpoint Signaling - Krenn, Veronica; Musacchio, Andrea (Frontiers in Oncology, 2015)
Aurora B, a member of the Aurora family of serine/threonine protein kinases, is a key player in chromosome segregation. As part of a macromolecular complex known as the chromosome passenger complex, Aurora B concentrates early during mitosis in the proximity of centromeres and kinetochores, the sites of attachment of chromosomes to spindle microtubules. There, it contributes to a number of processes that impart fidelity to cell division, including kinetochore stabilization, kinetochore-microtubule attachment, and the regulation of a surveillance mechanism named the spindle assembly checkpoint. In the regulation of these processes, Aurora B is the fulcrum of a remarkably complex network of interactions that feed back on its localization and activation state. In this review we discuss the multiple roles of Aurora B during mitosis, focusing in particular on its role at centromeres and kinetochores. Many details of the network of interactions at these locations remain poorly understood, and we focus here on several crucial outstanding questions.